Thioredoxin-dependent system. Application of inhibitors - Anna Jastrząb; Elżbieta Skrzydlewska (Taylor & Francis Group, 2021)
One of the systems responsible for maintaining cellular redox homeostasis is the thioredoxin-dependent system. An equally important function of this system is the regulation of the expression of many proteins by the transcription factor NF-κB or the apoptosis regulating kinase (ASK-1). Since it has been shown that the Trx-dependent system can contribute to both the enhancement of tumour angiogenesis and growth as well as apoptosis of neoplastic cells, the search for compounds that inhibit the level/activity of Trx and/or TrxR and thus modulate the course of the neoplastic process is ongoing. It has been shown that many naturally occurring polyphenolic compounds inactivate elements of the thioredoxin system. In addition, the effectiveness of Trx is inhibited by imidazole derivatives, while the activity of TrxR is reduced by transition metal ions complexes, dinitrohalobenzene derivatives, Michael acceptors, nitrosourea and ebselen. In addition, research is ongoing to identify new selective Trx/TrxR inhibitors.